2019
DOI: 10.1089/photob.2019.4628
|View full text |Cite
|
Sign up to set email alerts
|

“Photobiomics”: Can Light, Including Photobiomodulation, Alter the Microbiome?

Abstract: Objective: The objective of this review is to consider the dual effects of microbiome and photobiomodulation (PBM) on human health and to suggest a relationship between these two as a novel mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 170 publications
(177 reference statements)
4
47
0
2
Order By: Relevance
“…The effect of PDT on the oral microbiome has been only minimally investigated. Reports based on studies in mice 54,55 and humans 56,57 have shown that photobiomodulation (therapeutical application of low levels of red and/or near-infrarated light) may positively affect the human microbiome 54 . Additionally, studies investigating the effect of antibacterial PDT on oral bacteria have shown that various photosensitizers may exercise various www.nature.com/scientificreports www.nature.com/scientificreports/ effects on oral pathogens inducing selective biofilm inactivation 58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…The effect of PDT on the oral microbiome has been only minimally investigated. Reports based on studies in mice 54,55 and humans 56,57 have shown that photobiomodulation (therapeutical application of low levels of red and/or near-infrarated light) may positively affect the human microbiome 54 . Additionally, studies investigating the effect of antibacterial PDT on oral bacteria have shown that various photosensitizers may exercise various www.nature.com/scientificreports www.nature.com/scientificreports/ effects on oral pathogens inducing selective biofilm inactivation 58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in the bene ts of IR exposure to bone health have been widely investigated. It is generally accepted that IR can effectively increase the activity of cytochrome oxidase and mitochondrial ATP production, and accelerate bone formation by increasing local vascularization and the organization of collagen bers [28,30] . However, these processes are not just manifested in bone tissue to explain the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Juanita Anders (President of the American Society for Laser Medicine and Surgery) and colleagues argued for the acceptance of the specific term "photobiomodulation," as opposed to say, low-level light/laser therapy, for the use of non-ionizing EM radiation (mostly visible and infrared) as adjuvant clinical therapy (e.g., wound healing, anti-inflammatory) [144]. Recently, the term "photobiomics" has been introduced to recognize the effects of light therapy on the microbiome [145]. The ideas behind this type of photomedicine (using light for clinical benefit), however, were introduced far earlier.…”
Section: Photobiomodulation Effects On Human Healthmentioning
confidence: 99%